DESIGNING PURCHASING APPLICATION FOR PT OMEGA NUSA ERA BASED ON ANDROID - Ignatius Adrian Mastan; Melvina Sesilia (Universitas Teknokrat Indonesia, 2023)
PT Omega Nusa Era is a production company that collaborates with many suppliers as suppliers of raw materials needed to carry out their production. The large number of suppliers who need to be contacted to get raw materials hampers the company's goods production process. Therefore, it is necessary to develop a system that can help overcome these problems. This research begins with data collection by conducting interviews, literature studies, observation, and similar studies. Furthermore, system development uses the method Mobile Application Development Life Cycle Model (MADLC) which includes Identification, Design, Development, Prototyping, Testing, Deployment, and Maintenance Phase. System design using Object Oriented Programming (OOP) approached with Unified Modeling Language tools (UML) and application design using software Android Studio.This application is expected to help with the problem of ordering efficiency for raw materials produced by the PT Omega Nusa Era company by providing features for managing stock warehouse and selecting the items you want to order in one application, so you don't waste time contacting many suppliers to order goods. The conclusion obtained from this research is that this product purchase application can help overcome the problem of ordering goods faced by companies with various menus and features contained in the application